Synthesis of biologically active copper oxide nanoparticles as promising novel antibacterial-antibiofilm agents - Erci, Fatih; Cakir-Koc, Rabia; Yontem, Mustafa; Torlak, Emrah (TAYLOR & FRANCIS INC, 2020)
In this study, we aimed to synthesize copper oxide nanoparticles (CuONPs) mediated by plant extract in an environmentally friendly way and to reveal their potential biological activities. Here we synthesized CuONPs by using different concentrations of aqueous leaf extract of Thymbra spicata at 80 degrees C to obtain Ts1CuONPs and Ts2CuONPs. Biosynthesized nanoparticles were characterized by using UV-Vis, AFM, FTIR, SEM-EDS, TEM, DLS and zeta potential analysis. The antibacterial activity of the nanoparticles was determined by calculation of the inhibition zone and minimum inhibitory concentration against selected bacterial strains. Moreover, the antioxidant activity of the as-synthesized nanoparticles was evaluated based on DPPH radical scavenging activity. The results indicate that the as-synthesized NPs have an average size of 26.8 and 21 nm for Ts1CuONPs and Ts2CuONPs, respectively. The formed CuONPs have more antibacterial action on gram-positive bacteria compared to gram-negative bacteria. In addition, CuONPs demonstrated good inhibition activity against biofilm formation of Staphylococcus aureus (S. aureus). Furthermore, the results showed that the smaller size of the CuONPs caused the higher cytotoxicity on L929 mouse fibroblast cells. The as-synthesized CuONPs exhibit antibacterial and antibiofilm potential against S. aureus, indicating that they may be attractive candidates to use in future therapeutic applications.
Keywords: Antibacterial; antibiofilm; biosynthesis; copper oxide nanoparticles; cytotoxicity; ONE-POT SYNTHESIS; GREEN SYNTHESIS; LEAF EXTRACT; MEDIATED SYNTHESIS; ANTIOXIDANT; MECHANISMS; TOXICITY; BIOFILMS; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology